Adsorption Thermodynamics, Modeling, and Kinetics Studies for the Removal of Lead Ions Using ZnO Nanorods - Sadia Ata; Anila Tabassum; Ifra Shaheed; Ijaz ul Mohsin; Norah Alwadai; Maryam Al Huwayz; Munawar Iqbal; Arif Nazir (Adsorption Science & Technology)
In the present investigation, zinc oxide nanorods (ZnO-NR) were synthesized via the hydrothermal method using ZnCl2 as a zinc ion precursor in the presence of cetyltrimethylammonium bromide. Synthesized ZnO-NR was featured using advanced techniques including XRD, PL, SEM, and UV-visible spectroscopy. The role of these assynthesized ZnO-NR was evaluated for the sequestration of lead ions in batch mode. The elimination of lead ions was achieved at pH 6-7 using a 0.06 g adsorbent dose, 25 min contact time, 25 mg/L initial lead ion concentration, 323 K temperature, and 200 rpm agitation speed. A thermodynamic study revealed the endothermic nature of lead ion sequestration onto ZnO-NR. The lead ion sequestration followed kinetic (pseudo-second-order) and isotherm (Langmuir) models. The lead ions were eliminated up to 142 mg/g at the optimum level of affecting variables. The ZnO-NR might be a potential adsorbent for lead ion removal from industrial effluents.